Research Laboratories for Territorial Development - Antonio Taccone (ArcHistoR Architettura Storia Restauro: Architecture History Restoration, 2020)
The paper intends to illustrate the results of the C.a.pa.city project (Care Abilities and Professions for an Aggregating CITY,) presented in the framework of the 1st Call for Proposals of the Urban Innovative Actions (UIA) for the improvement of a circular economy system by urban and community regeneration in the suburbs of Reggio Calabria. The project has been outlined by the Lastre Laboratory (Integrated Laboratory of the Area for the development of the territory) of the PAU Department, in partnership with the Municipality of Reggio Calabria (Leader Partner),with Arci, and the Camera di Commercio. The topics included in this experience concern, in various aspects, planning strategies for the territory and the city by a research laboratory, as an opportunity to measure oneself with complex territorial systems, urban systems in affirmation in the continuous search for new roles and at the same time interdependent as elements of a network governed by solidarity phenomena, that is, those that take on a precise meaning precisely from the essence and resonance of their relationships. The method used is that of participatory forums and design ateliers that suggest various urban desires to better understand the demands of the contemporary city with a single common thread, namely the search for actions that respond to the demands of an eco-sustainable city.